2018
DOI: 10.22159/ijpps.2018v10i2.21834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metformin and Serratiopeptidase in Obese Patients With Knee Osteoarthritis

Abstract: Objective: Knee osteoarthritis is a common disabling chronic disease globally. Many pharmacological agents have been used efficiently in treatment of knee osteoarthritis. This study aims to evaluate metformin and serratiopeptidase together in treatment and stop of osteoarthritis progression by different mechanisms. Methods:Present study was a randomized clinical trial study conducted in Al-Kindi teaching hospital through the period from 1 st January to 30 th of May, 2017 on two groups of 80 osteoarthritis pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…Identifying the superiority of the phonophoresis technique to conventional US in OA was conducted using the piroxicam gel, 10 min of treatment per session and mild to moderate degree of knee OA. Results from this study showed that phonophoresis was superior to conventional US and also confirmed the findings of previous reports regarding factors influencing the quality and efficacy of phonophoresis [11,19].…”
Section: Monisha Et Alsupporting
confidence: 91%
See 1 more Smart Citation
“…Identifying the superiority of the phonophoresis technique to conventional US in OA was conducted using the piroxicam gel, 10 min of treatment per session and mild to moderate degree of knee OA. Results from this study showed that phonophoresis was superior to conventional US and also confirmed the findings of previous reports regarding factors influencing the quality and efficacy of phonophoresis [11,19].…”
Section: Monisha Et Alsupporting
confidence: 91%
“…Knee OA is a common disabling chronic disease globally [11]. OA is a non-inflammatory joint disease, it affects all joints most commonly affected are hip and knee joints, and the affected age group is elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…Serratiopeptidase is a natural molecule that is being used for decades, hence commonly considered as safe. The safety of this enzyme in different areas of therapeutics is supported by several studies [ 15 , 19 , 22 , 48 , 54 , 72 ] in which no side effects or adverse events were reported. However, some studies have reported adverse effects of this molecule, but at a rare frequency.…”
Section: Absorption and Safety Of Serratiopeptidasementioning
confidence: 80%
“…Serratiopeptidase can be used to treat osteoarthritis in combination with metformin. Ateia et al [ 62 ] reported the impact of metformin and serratiopeptidase on knee osteoarthritis in obese patients. Metformin and serratiopeptidase combination tablets were efficient in the treatment of knee osteoarthritis.…”
Section: Therapeutic Aspects Of Serratiopeptidasementioning
confidence: 99%